The Hypertext as the Reality. Communication and Language in the Polish and German Virtual Countries – the Outline of a Dissertation - Bierzyński, Zbigniew (Free your mind: Reflections on language, literature and culture, 2022)
This paper presents an idea of doctoral dissertation. Its study subject is the Polish and German language virtual countries that imitate the society and politics in the Internet. Until now, sociology, anthropology and communication sciences have been interested in the virtual countries phenomenon that offers the interesting possibilities for the textual studies and linguistics too. The main proposed in the dissertation thesis is the hypertext creates the virtual countries reality, because the hypertext combines the sign and its matter in contrast to the real world. Furthermore, the author suggests the deeper research into communication, structure and multimodal ways of creating the virtual community from comparing perspective – the question of typology of the Polish and German virtual countries and their cultural components. In addition, in the article it is shown the nascent in the German textual studies new scientific subbranch – image linguistics (German: Bildlinguistik) and it is paid the attention to low interest of the Polish textual linguists in the hypertext phenomenon, multimodality and image-text relations.